2016
DOI: 10.1177/0271678x16653614
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-asymmetry of cerebral blood flow in arterial spin labeling caused by unilateral fetal-type circle of Willis: Technical limitation or a way to better understanding physiological variations of cerebral perfusion and improving arterial spin labeling acquisition?

Abstract: In the recently published article, "Unilateral fetal-type circle of Willis anatomy causes right-left asymmetry in cerebral blood flow with pseudo-continuous arterial spin labeling: A limitation of arterial spin labeling-based cerebral blood flow measurements?", it was shown by the method of arterial spin labeling (ASL) that unilateral fetal-type circle of Willis could induce variation of blood flow in cerebellar and posterior cerebral artery territory. We believe that the reported observation, rather than bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The former was identified to be significantly higher compared with the latter. In theory, the hemodynamic changes of the circle of Willis would be more complex if FTP was combined with other variations ( 17 ). Previous studies have reported that anatomical variations of the circle of Willis, including persistent trigeminal artery, arterial window and anterior cerebral artery (ACA) -A1 dysplasia or absence, are associated with the occurrence of intracranial aneurysm ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…The former was identified to be significantly higher compared with the latter. In theory, the hemodynamic changes of the circle of Willis would be more complex if FTP was combined with other variations ( 17 ). Previous studies have reported that anatomical variations of the circle of Willis, including persistent trigeminal artery, arterial window and anterior cerebral artery (ACA) -A1 dysplasia or absence, are associated with the occurrence of intracranial aneurysm ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…These macrovascular alterations in arterial transit produce congenitally asymmetric blood delivery with varying contributions from the anterior/posterior circulations and incomplete collateralization, particularly at short PLDs. Longer‐delay ASL or MR angiography can help to resolve this source of perfusion “pseudo‐asymmetry.” 2,35 …”
Section: Technique and Artifactsmentioning
confidence: 99%
“…Longer-delay ASL or MR angiography can help to resolve this source of perfusion "pseudo-asymmetry." 2,35 Misclassification of voxels can occur in a variety of circumstances. When extracranial tissues are not masked, asymmetric nasal mucosal perfusion can be identified.…”
Section: Range Of Target Velocitiesmentioning
confidence: 99%
“…One common and easily recognizable situation that is associated with focal decreased ASL signal (AKA decreased CBF) is fetal posterior cerebral artery (PCA) where there is decreased CBF because of delayed transit time. It is important to recognize that focally decreased ASL signal is a nonspecific finding and can be seen in various clinical situations such as TIA, migraine (aura state or early phase), [50][51][52] seizure (interictal stage), 53 variant anatomy (such as fetal PCA), 54,55 Partial Volume Averaging (PVE) artifact, 56,57 and infection. 58 Most of these situations are recognizable by considering the clinical history and identifying (e.g., with MR angiogram) anatomic variants that may be associated with delayed transit time corresponding to the area of decreased ASL signal.…”
Section: Strokementioning
confidence: 99%